A Brave New World! - Arulselvi, Uthayakumaran; Nursyaheedah, Muhammad Isa (2018)
Kuantan, 7 September 2018 - The Centre for Modern Languages and Human Sciences (CMLHS) in collaboration with Faculty of Industrial Sciences (FIST) alongside Jabatan Pendidikan Negeri Pahang, Bahagian Teknologi Pendidikan Negeri Pahang, Kementerian Pendidikan Malaysia and Jabatan Hal Ehwal Korporat & Kualiti UMP joined hands to conduct the Fun in English programme in conjunction with Kem Saintis Muda 2018 for secondary school students.